Communication Strategies in Overcoming OGBV Through Gender Equality-Based Digital Literacy: A Case Study in Tangerang City - Elyana, Korry; Ramdana, Ilham; Khikmawanto, Khikmawanto (Dinasti International Journal of Economics, Finance & Accounting, 2026)
(Online Gender-Based Violence (OGBV) in Tangerang City has become a serious threat to women and vulnerable groups, with three dominant forms: grooming, sexual extortion, and the dissemination of non-consensual personal content. This research uses a descriptive qualitative approach through interviews with DP3AP2KB, Diskominfo, and social practitioners, as well as social media content analysis. The results showed that the main factors causing OGDV include low digital literacy, gender inequality, and weak reporting systems. The Tangerang City Government has implemented digital literacy programs and campaigns through the Digital Festival, but challenges such as low early detection, social stigma, and inter-agency coordination still hinder the effectiveness of the treatment. This study recommends prevention strategies based on gender equality, strengthening integrated reporting systems, and multi-stakeholder collaboration to create a safer digital space.